PENGARUH KOMPENSASI DAN PENGEMBANGAN KARIR TERHADAP TURNOVER INTENTION MELALUI KOMITMEN ORGANISASI PADA PT SURYA MADISTRINDO SURABAYA - Heru Kristanto; Bethsheba Adelia Hastanti (Department of Management - Institut Shanti Bhuana, 2023)
This study aims to analyze the influence of compensation and career development on turnover intention. It analyzes the impact of compensation and career development on turnover intention through organizational commitment at PT Surya Madistrindo. This study uses a quantitative approach. The research design falls under the category of causal research. The population for this study consists of 115 employees at PT Surya Madistrindo. The sampling method used in this study is saturated sampling, resulting in a sample size of 100% of the population, which is 115 respondents. Based on the analysis using Partial Least Square (PLS), the results show that compensation and organizational commitment have a significant negative effect on turnover intention. However, career development does not have a significant effect on turnover intention at PT Surya Madistrindo. Compensation and career development have a positive and significant effect on organizational commitment at PT Surya Madistrindo. Indirectly, organizational commitment is found to mediate the relationship between compensation and turnover intention, but it has not been able to mediate the effect of career development on turnover intention at PT Surya Madistrindo.